Robotic and laparoscopic reconstructive surgery in children and adults - Ost, Michael C.; SpringerLink (Online service). (Totowa, N.J. Humana London Springer [distributor], 2011)
Robotic and Laparoscopic Reconstructive Surgery In Children and Adults is a unique volume focusing on the union between adult and pediatric urologic surgical techniques. The breadth of this wonderful convergence is most clearly and consistently demonstrated when minimally invasive reconstructive techniques are utilized. This volume describes in detail the surgical steps of the major adult and pediatric reconstructive laparoscopic and robotic cases. Pediatric urologists, adult urologists, fellows, and urology residents will find this volume to be a comprehensive, yet concise, reference for most all robotic and laparoscopic procedures that may be performed within this vast discipline.
Laparoscopic and robotic instrumentation for urologic reconstructive surgery in adults -- Instrumentation during pediatric robotic anastomoses and reconstruction -- Instrumentation during pediatric laparoscopic robotic anastomoses and reconstruction -- Adult laparoscopic partial nephrectomy for renal cell carcinoma -- Adult robotic-assisted partial nephrectomy for renal cell carcinoma -- Pediatric laparoscopic and robotic upper pole nephrectomy for nonfunctioning moieties -- Adult laparoscopic and robotic-assisted pyeloplasty for ureteropelvic junction obstruction -- Pediatric laparoscopic (infant, pre-pubertal, and teenager) pyeloplasty for ureteropelvic junction obstruction -- Pediatric robotic (infant, pre-pubertal, and teenager) pyeloplasty for ureteropelvic junction obstruction -- Laparoscopic ureteroureterostomy and correction of ureteral defects -- Robotic ureteroureterostomy and correction of ureteral defects -- Robotic radical cystectomy and use of intestinal segments for reconstruction in the adult patient -- Laparoscopic bladder augmentation and creation of continent-catheterizable stomas in the pediatric patient -- Laparoscopic ureteral reimplant surgery to correct reflux disease -- Robotic ureteral reimplant surgery to correct reflux disease -- Laparoscopoic and robotic orchiopexy for the impalpable undescended testicle -- Laparoscopic anastomoses and bladder neck reconstruction following radical prostatectomy -- Robotic anastomoses and bladder neck reconstruction following radical prostatectomy -- The role of NOTES and LESS in minimally invasive reconstructive urological surgery -- Laparoscopy and robotics in stress urinary incontinence and pelvic reconstructive surgery.
Electronic reproduction.
Keywords: Laparoscopy -- methods; Reconstructive Surgical Procedures -- methods; Robotics; Genitourinary organs -- Surgery; Laparoscopic surgery; Electronic book